Spektrum kebijakan pertanian Indonesia. Telaah struktur, kasus, dan alternatif strategi - ARIFIN, Bustanul (Erlangga, 2001)
Spektrum kebijakan pertanian Indonesia. Telaah struktur, kasus, dan alternatif strategi